On the width of the recombination zone in ambipolar organic field effect transistors - Kemerink, Martijn; Charrier, Dimitri S. H.; Smits, E. C. P.; Mathijssen, Simon G. J.; Leeuw, Dago M. de; Janssen, René A. J. (Applied physics letters, 2008)
The performance of organic light emitting field effect transistors is strongly influenced by the width of the recombination zone. We present an analytical model for the recombination profile. By assuming Langevin recombination, the recombination zone width WWW is found to be given byW=4.34dδ⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯√W=4.34dδW=<msqrt>4.34dδ</msqrt>, with ddd and δδδ the gate dielectric and accumulation layer thicknesses, respectively. The model compares favorably to both numerical calculations and measured surface potential profiles of an actual ambipolar device.
Gesehen am 11.12.2019